2012
DOI: 10.1093/ntr/nts208
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Sensitivity as a Predictor of Acute Subjective Effects of Smoking

Abstract: introduction: Anxiety sensitivity (i.e., AS; the degree to which one believes that anxiety and its related sensations are harmful) is a stable trait that is associated with habitual smoking. Yet, the mechanisms linking AS and smoking are unclear. A promising hypothesis is that high-AS individuals are more sensitive to the acute subjective reinforcing effects of smoking and are, therefore, more prone to tobacco dependence. This study examined trait AS as a predictor of several subjective effects of cigarette sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Importantly, high anxiety sensitivity is related to greater odds of early smoking lapse (12) and relapse during quit attempts (13). These observed anxiety sensitivity-smoking relations are not better explained by smoking rate, sex, other concurrent substance use, panic attack history, or trait-like negative mood propensity (6,7). …”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Importantly, high anxiety sensitivity is related to greater odds of early smoking lapse (12) and relapse during quit attempts (13). These observed anxiety sensitivity-smoking relations are not better explained by smoking rate, sex, other concurrent substance use, panic attack history, or trait-like negative mood propensity (6,7). …”
Section: Introductionmentioning
confidence: 71%
“…Specifically, anxiety sensitivity is positively correlated with smoking motives to reduce negative affect (5) and beliefs that smoking will reduce negative affect (6). Similarly, higher levels of anxiety sensitivity are associated with increases in positive affect after smoking (7), and smoking reduces anxiety in high anxiety sensitivity smokers who smoked during stress exposure (8). Moreover, smokers higher in anxiety sensitivity, relative to those with lower anxiety sensitivity, perceive quitting as more difficult (9) and experience more intense nicotine withdrawal during early phases in quitting (10).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this possibility, one experimental study reported that AS was related to smoking-induced increases in PA during tobacco non-abstinence. [63] …”
Section: Discussionmentioning
confidence: 99%
“…Greater interoceptive awareness in AS and GAD could result in increased awareness of internal sensations produced by the acute pharmacological (e.g., stimulation, arousal enhancement) and sensory (e.g., sensations of inhaling smoke or imbibing alcohol) effects of self-administering drugs of abuse, which could in turn alter the profile of subjective drug effects. Although this hypothesis has not been tested, one study in adult regular smokers found that AS was associated with greater subjective positive effects from acute cigarette administration (Wong, et al, 2013). Additionally, some work in emerging adults has negatively correlated AS with cannabis use, which could theoretically be due to greater negative subjective effects of cannabis in high-AS individuals (S.…”
Section: Introductionmentioning
confidence: 99%